Opening and officiating speech 2023 virtual three-minute thesis competition / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
Alhamdulillah, praise be to Allah S.W.T for His blessings which made it possible for us to gather today at this year's national-level Virtual Three-Minute Thesis (3MT) Competition. First and foremost, I would like to thank Universiti Kebangsaan Malaysia (UKM) for joining hands with UiTM to host this meaningful event. A very warm welcome and 'Selamat Datang' to all eminent guests, distinguished judges, and participants to this Virtual 3MT Competition.3MT is an international research and academic communication competition to help students improve their academic presentation and professional communication skills.